Promoting Students’ Motivation in Learning English Vocabulary through a Collaborative Video Project - Tryanti R. Abdulrahman; Noni Basalama (Soegijapranata Catholic University, 2019)
The main objective of this study was to motivate EFL (English Foreign Language) students in learning English vocabulary by using collaborative video Project. This study followed a case study methodology to describe how video project experience can engage students to learn English and provide them an opportunity to participate in tasks as well as enrich their vocabulary. Twenty-five EFL students in the Vocabulary Building Course (VBC) participated in this study. This study used three phases for evaluations: the pre-production phase, production phase and post production phase. Data were collected from classroom observations, the video Project process and document analyses. A summary of the findings related to the video theme and narrative analysis of students’ videos are presented in this paper. Data analysis showed that students responded differently to their video project assignments and produced different types of collaborative videos with the help of a camcorder and computer application. Then, a survey was conducted to collect feedback from participants to learn their opinions and attitudes regarding the use of collaborative video project, students’ learning and motivation. Participants in this study expressed positive attitudes and opinions toward their video-project experiences. This study demonstrates that video Project can be a great tool for promoting students’ motivation and participation in learning English, enriching their vocabulary and can be an effective and powerful tool to create fun, interactive, and collaborative learning environments.